Validation of the quantitation methods of 1-(β-phenylethyl)-4-amino-1,2,4triazole bromide substance by spectrophotometric method - Kucherenko, L. I.; Parniuk, N. V.; Khromylova, O. V.; Кучеренко, Людмила Іванівна; Парнюк, Наталя Вікторівна; Хромильова, Ольга Володимирівна (India: Innovare Academic Sciences Pvt. Ltd., 2018)
Objective: The aim of the work was to determine the validation characteristics for the developed method of quantitation of 1-(β-phenylethyl)-4amino-1,2,4-triazole bromide substance by absorption spectrophotometry in the ultraviolet region (UV). Methods: For study purposes, the 1-(β-phenylethyl)-4-amino-1,2,4-triazole bromide substance and the standard sample, obtained by the state enterprise “plant of chemical reagents” of scientific and technological complex “institute of single crystals” of the National Academy of Sciences of Ukraine, was used. In the course of our work, we used chemical, physical, physicochemical (absorption spectrophotometry in the UV region), and statistical methods of analysis. The study was carried out at the Laboratory for Standardization and Technology of Medicines at the Department of Pharmaceutical Chemistry at Zaporizhzhia State Medical University (Ukraine). Results: In the previous studies, we have developed a technique for spectrophotometric determination of the quantitative content of 1-(β-phenylethyl)4-amino-1,2,4-triazole bromide substance. The results of the studies showed that the absorption curve in the UV region of the substance solution has three absorption maxima, namely: λ1=252 nm, λ2=258 nm, and λ3=263 nm. To quantify the substance, the wavelength λ2=258 nm was used. The results of the quantitation of the 1-(β-phenylethyl)-4-amino-1,2,4-triazole bromide substance by spectrophotometric method prove that the technique developed by us is accurate and reproducible and meets the current requirements. To the developed methodology to ensure accurate and accurate analysis results, its validation was carried out. According to the requirements of the State Pharmacopoeia of Ukraine (2 editions), the developed method for quantitation of the substance was checked for such validation characteristics as specificity, linearity, range of application, accuracy, correctness, and robustness. Conclusions: As a result of the work, it was proved that the method of quantitation of 1-(β-phenylethyl)-4-amino-1,2,4-triazolе bromide substance by spectrophotometric method is valid.
Keywords: arterial hypertension; spectrophotometry; quantitation; validation; 1-(β-phenylethyl)-4-amino-1,2,4-triazole bromide